Titanium diboride reinforced boron carbide-based bulletproof ceramic and its preparation method and application
By adding titanium diboride and appropriate additives to boron carbide ceramics and using discharge plasma sintering method, the problems of high sintering temperature and low density of boron carbide ceramics were solved, and boron carbide-based bulletproof ceramic inserts with high hardness, high strength and high toughness were prepared, which improved its bulletproof performance and safety of use.
Patent Information
- Application Number
- CN202310446095.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-24
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-04-24
AI Technical Summary
During the sintering process, boron carbide ceramics have problems such as high sintering temperature, low density after sintering, and poor fracture toughness, which affects the use effect and application cost of its bulletproof insert.
By using titanium diboride as a reinforcement, adding appropriate additives and controlling the sintering process, a boron carbide-based bulletproof ceramic insert with high hardness, high strength and high toughness was prepared.
The high hardness, strength and toughness of boron carbide-based bulletproof ceramic inserts are achieved, which improves its anti-elastic bending and protective performance, reduces density, reduces user physical consumption, and enhances user flexibility and safety.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of bulletproof metal ceramics, and in particular relates to a titanium diboride (TiB2) reinforced boron carbide (B4C) based bulletproof ceramic insert plate and a preparation method and application thereof. Background Art
[0002] Boron carbide, also known as black (diamond), is the third hardest material after diamond and cubic boron nitride, so it has become an important member of the superhard material family. Boron carbide, as a new type of non-oxide ceramic material, is widely used in energy, military, nuclear energy and bulletproof fields because of its high melting point, high hardness, low density, good thermal stability, strong resistance to chemical corrosion and strong neutron absorption. Boron carbide bulletproof materials have been widely used in individual bulletproof vests, bulletproof armor, armored belly plates of armed helicopters, and police and civilian special vehicles. At present, boron carbide bulletproof materials are mainly prepared by sintering. Pure boron carbide usually has problems such as high sintering temperature required for densification, low density of ceramics obtained after sintering, and poor fracture toughness during the sintering process. In industry, pressureless sintering, hot pressing sintering, hot isostatic pressing sintering, reaction sintering and other technologies are generally used to sinter boron carbide. By improving the sintering process and adding sintering aids, the mechanical properties of boron carbide are improved, laying the foundation for further research on the sintering process of boron carbide.
[0003] Boron carbide ceramics are the lowest density, the highest hardness, and the higher elastic modulus among conventional bulletproof insert plate ceramic materials (conventional boron carbide, aluminum oxide, silicon carbide) on the market, and also have the neutron absorption ability that other ceramic materials do not possess, making it the preferred of ceramic bulletproof insert plate. However, the processing technology of boron carbide ceramics is high, high temperature and high pressure sintering is required, and toughness is poor, brittleness is large, which is unfavorable for the secondary use of bulletproof insert plate, affecting the use effect of ceramic bulletproof insert plate, further improving its application cost, and limiting its wide application as single-phase protective armor. Titanium diboride is a ceramic material with high density, high hardness, high temperature strength, and good stability, and it has good physical and chemical compatibility with boron carbide, and adding it to boron carbide-based bulletproof ceramic insert plate can play a very strong hardening and strengthening effect, and the enhanced titanium boride-based bulletproof ceramic insert plate hardness obtained is higher, but the toughness of two kinds of ceramic materials is all poor, therefore, the toughness problem after the combination of these two kinds of ceramic materials becomes the research focus of the present invention researchers, and this is also the necessary performance that ceramic bulletproof insert plate needs to have.
[0004] The researchers of the present invention use titanium diboride as a reinforcing agent, add appropriate additives, a second phase, and control the sintering process to retain the low density and high strength of the obtained boron carbide-based bulletproof ceramic insert, while greatly improving the toughness and impact, thereby obtaining a bulletproof ceramic insert with anti-bullet and anti-bending properties. At present, there is no report on the preparation of boron carbide-based ceramic materials using this technology and their application in the field of bulletproof inserts. Summary of the invention
[0005] The main purpose of the present invention is to provide a titanium diboride reinforced boron carbide-based bulletproof ceramic, which has high hardness, high strength, high toughness, is not easy to break, and its preparation method is simple and easy to operate. It can be used in bulletproof plug plates, has excellent anti-ballistic performance and anti-bending performance, and can improve the protective performance of the bulletproof plug plates.
[0006] In order to achieve the purpose of the present invention, the present invention provides a titanium diboride reinforced boron carbide-based bulletproof ceramic, which is composed of the following raw materials in mass percentage: 62-82% of boron carbide, 10-16% of titanium diboride, 4-19% of silicon carbide, 0.5-3% of tungsten powder and 1-5% of titanium powder;
[0007] The titanium diboride reinforced boron carbide-based bulletproof ceramic is formed by spark plasma sintering.
[0008] Furthermore, the purity of the tungsten powder is 99.9-99.99%, and the average particle size is 0.8-5.0 μm;
[0009] The purity of the titanium diboride is 98.5-99.9%, and its average particle size is ≤1.0 μm;
[0010] The purity of the boron carbide is 98-99.5%, and its average particle size is ≤1.0 μm;
[0011] The purity of the silicon carbide is 98.5-99.9%, and its average particle size is less than 1.0 μm;
[0012] The purity of the titanium powder is 99.0-99.9%, and the average particle size thereof is ≤5.0 μm.
[0013] The present invention also provides a method for preparing titanium diboride reinforced boron carbide-based bulletproof ceramics, which specifically comprises the following steps:
[0014] S1. Add titanium diboride, silicon carbide, tungsten powder and titanium powder to the boron carbide matrix, mix well, ball mill, and dry to obtain a boron carbide mixture;
[0015] S2. Place the above boron carbide mixture in a sintering furnace, heat it to 700-900°C under vacuum conditions, then fill it with inert gas, and heat it to 1600-1800°C at 30-50MPa under the protection of inert gas, sinter it by spark plasma, and cool it naturally to room temperature to obtain.
[0016] Furthermore, in the ball milling process, the ball milling medium is anhydrous ethanol, the cemented carbide balls used for ball milling are zirconia balls, the ball milling speed is 400-600 r / min, the mass ratio of zirconia balls, materials and medium is 8-12:1:1.5, and the ball milling time is 5-10 hours.
[0017] Furthermore, the vacuum degree under the vacuum conditions is -0.08MPa to -0.09MPa.
[0018] Furthermore, the spark plasma sintering time is 10 to 20 minutes.
[0019] The titanium diboride reinforced boron carbide-based bulletproof ceramic provided by the present invention can be applied to bulletproof insert plates.
[0020] The present invention has achieved the following beneficial effects:
[0021] 1. The present invention uses boron carbide as a matrix, titanium diboride as a reinforcement, silicon carbide, tungsten powder, and titanium powder as additives. After ball milling and mixing, the mixture is heated under vacuum conditions to remove impurities, and then the titanium diboride-reinforced boron carbide-based bulletproof ceramic is obtained by spark plasma sintering. The titanium diboride-reinforced boron carbide-based bulletproof ceramic has the advantages of high hardness, high strength, high toughness, high temperature stability, etc., and maintains a relatively low density, so that the prepared bulletproof insert can not only ensure high bulletproof performance, but also is not easy to break after shooting bulletproof, and can also reduce the user's physical exertion, increase the user's flexibility, and ensure that the user uses it more safely.
[0022] 2. The titanium diboride reinforced boron carbide-based bulletproof ceramic of the present invention has the performance of high hardness and high strength, mainly because the addition of titanium diboride inhibits the grain growth of the boron carbide mixture during the sintering process, and through vacuum high-temperature impurity removal, under the premise of ensuring density, through the spark plasma sintering process, the sintering temperature is reduced, the grain growth time is shortened, and the boron carbide-based ceramic with fine and uniform grains is obtained, so that it has higher hardness, strength and toughness, and has higher anti-ballistic performance.
[0023] 3. The present invention enhances the physical and chemical compatibility between titanium diboride and boron carbide by adding silicon carbide, tungsten powder and titanium powder in appropriate proportions as additives, reduces the porosity of boron carbide-based ceramics, improves the density of the ceramic material of the present invention, improves the toughness of boron carbide-based ceramics, makes it have higher fracture toughness and elastic modulus, improves the anti-multiple-strike performance and stress wave transmission ability of the bulletproof plate product of the present invention, and significantly enhances the anti-ballistic performance of the ceramic bulletproof plate.
[0024] 4. Compared with conventional boron carbide-based bulletproof ceramics, the present invention has higher hardness, strength and toughness. The bulletproof performance of the bulletproof ceramics is further improved through grain refinement and particle strengthening. The present invention adopts a spark plasma sintering method to combine titanium diboride, boron carbide, silicon carbide and other components at a relatively low temperature. The sintering temperature is low, the sintering time is short, the process is controllable, and the obtained product has high density and excellent comprehensive performance, and can be widely used in protective armor.
[0025] 5. The titanium diboride reinforced boron carbide-based bulletproof ceramic prepared by the present invention using boron carbide, titanium diboride, silicon carbide, tungsten powder and titanium powder with high purity and nanometer particle size has a density of 2.59-2.78g / cm3, a hardness of 40-48GPa, and a fracture toughness of 7.5-13.5MPa·m 1 / 2. The elastic modulus is 620-710GPa and the flexural strength is 900-1450Mpa. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The polyphenylene ether (PPE) alloy material used for an impeller of the present invention will be described below in conjunction with specific embodiments.
[0028] Example 1
[0029] The preparation method of titanium diboride reinforced boron carbide-based bulletproof ceramics is as follows:
[0030] (1) BC (purity of 99.5%, average particle size of 500 nm) was used as the matrix material, TiB2 (purity of 99.9%, average particle size of 1 μm) was used as the reinforcement, SiC (purity of 99.9%, average particle size of 800 nm), W powder (purity of 99.99%, average particle size of 800 nm) and Ti powder (purity of 99.9%, average particle size of 5 μm) were used as additives, and the ratio of BC4 to TiB2 was 62 wt%, 14.6 wt%, 18.8 wt% SiC, 1.5wt% W powder and 3.1wt% Ti powder are prepared and added into a ball mill for mixing. Anhydrous ethanol is used as a solvent and zirconium oxide balls are used to mix the mixture at a speed of 520 r / min for 8 hours. The mass ratio of the zirconium oxide balls, the materials (the materials in the present invention refer to a mixture of B4C, TiB2, SiC, W powder and Ti powder) and anhydrous ethanol is 10:1:1.5. After being mixed evenly, the mixture is dried at 200°C for 2 hours to obtain a boron carbide mixture.
[0031] (2) The boron carbide mixture is placed in a spark plasma sintering furnace, and under a vacuum condition of -0.09 MPa, the temperature is raised to 700°C at a rate of 50°C / min, and then 1 atm argon is quickly filled in, and the gas pressure in the sintering furnace is adjusted to 50 MPa, and then the temperature is raised to 1700°C at a rate of 100°C / min, and the temperature is kept for 15 minutes, the pressure is released, and the mixture is naturally cooled to room temperature to obtain the product.
[0032] The titanium diboride reinforced boron carbide-based bulletproof ceramic obtained above was tested and the density was 2.78 g / cm 3 , hardness is 42.3GPa, fracture toughness is 8.1MPa·m 1 / 2. The elastic modulus is 659GPa and the flexural strength is 1012Mpa.
[0033] Example 2
[0034] The preparation method of titanium diboride reinforced boron carbide-based bulletproof ceramics is as follows:
[0035] (1) B4C (purity of 98%, average particle size of 500nm) is used as the matrix raw material, TiB2 (purity of 99.9%, average particle size of 50nm) is used as the reinforcement, SiC (purity of 99.9%, average particle size of 800nm), W powder (purity of 99.99%, average particle size of 1μm) and Ti powder (purity of 99.9%, average particle size of 40nm) are used as additives, and the ratio of B4C to TiB2 is 82wt%, 10.5wt%, 5.2wt%, 1.5wt%, 2.5wt%, 3.5wt%, 5.5wt%, 6.5wt%, 7.5wt%, 8.5wt%, 1.5wt%, 2.5wt%, 3.5wt%, 5.5wt%, 6.5wt%, 7.5wt%, 8.5wt%, 7.5wt%, 8.5wt%, 8.5wt%, 3.5wt%, 6.5wt%, 7.5wt%, 8 ... % SiC, 0.8wt% W powder and 1.5wt% Ti powder are prepared, added into a ball mill for mixing, and anhydrous ethanol is used as a solvent. Zirconium oxide balls are used in the ball mill for mixing at a speed of 480r / min for 10 hours, wherein the mass ratio of the zirconium oxide balls, the materials (the materials in the present invention refer to a mixture of B4C, TiB2, SiC, W powder and Ti powder) and anhydrous ethanol is 10:1:1.5. After mixing evenly, the mixture is placed at 200°C for drying for 2 hours to obtain a boron carbide mixture.
[0036] (2) The boron carbide mixture is placed in a spark plasma sintering furnace, and under a vacuum condition of -0.08 MPa, the temperature is raised to 900°C at a rate of 50°C / min, and then 1 atm argon is quickly filled in, and the gas pressure in the sintering furnace is adjusted to 40 MPa, and then the temperature is raised to 1800°C at a rate of 100°C / min, and the temperature is kept for 15 minutes, the pressure is released, and the mixture is naturally cooled to room temperature to obtain the product.
[0037] The titanium diboride reinforced boron carbide-based bulletproof ceramic obtained above was tested and the density was 2.68 g / cm 3 , hardness is 45.6GPa, fracture toughness is 9.8MPa·m 1 / 2. The elastic modulus is 692GPa and the flexural strength is 1255Mpa.
[0038] Example 3
[0039] The preparation method of titanium diboride reinforced boron carbide-based bulletproof ceramics is as follows:
[0040] (1) B4C (purity of 99.5%, average particle size of 1 μm) was used as the matrix material, TiB2 (purity of 99.9%, average particle size of 1 μm) was used as the reinforcement, SiC (purity of 99.9%, average particle size of 800 nm), W powder (purity of 99.95%, average particle size of 200 nm) and Ti powder (purity of 99.9%, average particle size of 5 μm) were used as additives, and the ratio of B4C to TiB2 was 65.4 wt%, 16 wt%, 10.6 wt% and 10.6 wt%. t% SiC, 3.0wt% W powder and 5.0wt% Ti powder are prepared and added into a ball mill for mixing. Anhydrous ethanol is used as a solvent and zirconium oxide balls are used to mix the mixture at a speed of 600r / min for 10 hours. The mass ratio of zirconium oxide balls, materials (the materials in the present invention refer to a mixture of B4C, TiB2, SiC, W powder and Ti powder) and anhydrous ethanol is 12:1:1.5. After mixing evenly, the mixture is dried at 200°C for 2 hours to obtain a boron carbide mixture.
[0041] (2) The boron carbide mixture is placed in a spark plasma sintering furnace, and under a vacuum condition of -0.08 MPa, the temperature is raised to 800°C at a rate of 50°C / min, and then 1 atm argon is quickly filled in, and the gas pressure in the sintering furnace is adjusted to 40 MPa, and then the temperature is raised to 1650°C at a rate of 100°C / min, and the temperature is kept for 20 minutes, the pressure is released, and the mixture is naturally cooled to room temperature to obtain the product.
[0042] The titanium diboride reinforced boron carbide-based bulletproof ceramics obtained above were tested and the density was 2.75 g / cm 3 , hardness is 40.1GPa, fracture toughness is 7.5MPa·m 1 / 2. The elastic modulus is 620GPa and the flexural strength is 904Mpa.
[0043] Example 4
[0044] The preparation method of titanium diboride reinforced boron carbide-based bulletproof ceramics is as follows:
[0045] (1) B4C (purity of 99.5%, average particle size of 500nm) is used as the matrix material, TiB2 (purity of 99.9%, average particle size of 1μm) is used as the reinforcement, SiC (purity of 99.9%, average particle size of 800nm), W powder (purity of 99.99%, average particle size of 800nm) and Ti powder (purity of 99.9%, average particle size of 5μm) are used as additives, and the ratio of B4C to TiB2 is 75.3wt%, 15.6wt%, 4. 1wt% SiC, 0.5wt% W powder and 4.5wt% Ti powder are prepared and added into a ball mill for mixing. Anhydrous ethanol is used as a solvent and zirconium oxide balls are used to mix the mixture at a speed of 560r / min for 9 hours. The mass ratio of the zirconium oxide balls, the materials (the materials in the present invention refer to a mixture of B4C, TiB2, SiC, W powder and Ti powder) and anhydrous ethanol is 10:1:1.5. After being mixed evenly, the mixture is dried at 200°C for 2 hours to obtain a boron carbide mixture.
[0046] (2) The boron carbide mixture is placed in a spark plasma sintering furnace, and under a vacuum condition of -0.09 MPa, the temperature is raised to 800°C at a rate of 50°C / min, and then 1 atm argon is quickly filled in, and the gas pressure in the sintering furnace is adjusted to 40 MPa, and then the temperature is raised to 1710°C at a rate of 100°C / min, and the temperature is kept at this temperature for 20 minutes, the pressure is released, and the mixture is naturally cooled to room temperature to obtain the product.
[0047] The titanium diboride reinforced boron carbide-based bulletproof ceramics obtained above were tested and the density was 2.71 g / cm 3 , hardness is 43.8GPa, fracture toughness is 12.7MPa·m 1 / 2 , elastic modulus is 701GPa and flexural strength is 1309Mpa.
[0048] Example 5
[0049] The preparation method of titanium diboride reinforced boron carbide-based bulletproof ceramics is as follows:
[0050] (1) B4C (purity of 99.5%, average particle size of 500nm) is used as the matrix material, TiB2 (purity of 99.9%, average particle size of 1μm) is used as the reinforcement, SiC (purity of 99.9%, average particle size of 800nm), W powder (purity of 99.99%, average particle size of 800nm) and Ti powder (purity of 99.9%, average particle size of 5μm) are used as additives, and the ratio of B4C to TiB2 is 70.0wt%, 12.0wt%, 12. 0wt% SiC, 2.0wt% W powder and 4.0wt% Ti powder are prepared, added into a ball mill for mixing, and mixed at a speed of 560r / min for 9h in the ball mill using anhydrous ethanol as a solvent and zirconia balls, wherein the mass ratio of the zirconia balls, the materials (the materials in the present invention refer to a mixture of B4C, TiB2, SiC, W powder and Ti powder) and anhydrous ethanol is 10:1:1.5. After mixing evenly, the mixture is dried at 200°C for 2h to obtain a boron carbide mixture.
[0051] (2) The boron carbide mixture is placed in a spark plasma sintering furnace, and under a vacuum condition of -0.09 MPa, the temperature is raised to 800°C at a rate of 50°C / min, and then 1 atm argon is quickly filled in, and the gas pressure in the sintering furnace is adjusted to 40 MPa, and then the temperature is raised to 1710°C at a rate of 100°C / min, and the temperature is kept at this temperature for 20 minutes, the pressure is released, and the mixture is naturally cooled to room temperature to obtain the product.
[0052] The titanium diboride reinforced boron carbide-based bulletproof ceramic obtained above was tested and the density was 2.63 g / cm 3 , hardness is 44.6GPa, fracture toughness is 10.9MPa·m 1 / 2 , elastic modulus is 682GPa and flexural strength is 1357Mpa.
[0053] Example 6
[0054] The preparation method of titanium diboride reinforced boron carbide-based bulletproof ceramics is as follows:
[0055] (1) B4C (purity of 99.5%, average particle size of 500nm) is used as the matrix material, TiB2 (purity of 99.9%, average particle size of 1μm) is used as the reinforcement, SiC (purity of 99.9%, average particle size of 800nm), W powder (purity of 99.99%, average particle size of 800nm) and Ti powder (purity of 99.9%, average particle size of 5μm) are used as additives, and the ratio of B4C to TiB2 is 73.5wt%, 13.5wt%, 8. 5wt% SiC, 1.9wt% W powder and 2.6wt% Ti powder are prepared and added into a ball mill for mixing. Anhydrous ethanol is used as a solvent and zirconium oxide balls are used to mix the mixture at a speed of 560r / min for 9 hours. The mass ratio of the zirconium oxide balls, the materials (the materials in the present invention refer to a mixture of B4C, TiB2, SiC, W powder and Ti powder) and anhydrous ethanol is 10:1:1.5. After being mixed evenly, the mixture is dried at 200°C for 2 hours to obtain a boron carbide mixture.
[0056] (2) The boron carbide mixture is placed in a spark plasma sintering furnace, and under a vacuum condition of -0.09 MPa, the temperature is raised to 800°C at a rate of 50°C / min, and then 1 atm argon is quickly filled in, and the gas pressure in the sintering furnace is adjusted to 40 MPa, and then the temperature is raised to 1710°C at a rate of 100°C / min, and the temperature is kept at this temperature for 20 minutes, the pressure is released, and the mixture is naturally cooled to room temperature to obtain the product.
[0057] The titanium diboride reinforced boron carbide-based bulletproof ceramic obtained above was tested and the density was 2.59 g / cm 3 , hardness is 48.2GPa, fracture toughness is 13.5MPa·m 1 / 2 , elastic modulus is 715GPa and flexural strength is 1480Mpa.
[0058] Comparative Example 1
[0059] The preparation method of boron carbide-based bulletproof ceramics is the same as the preparation method of titanium diboride-reinforced boron carbide-based bulletproof ceramics in Example 6, and specific reference is made to Example 6. Unlike Example 6, in step (1) of this comparative example 1, B4C (purity of 99.5%, average particle size of 500nm) is used as the matrix raw material, SiC (purity of 99.9%, average particle size of 800nm), W powder (purity of 99.99%, average particle size of 800nm) and Ti powder (purity of 99.9%, average particle size of 5μm) are used as additives, and the ingredients are prepared according to 87.0wt% B4C, 8.5wt% SiC, 1.9wt% W powder and 2.6wt% Ti powder.
[0060] After testing, the density of the boron carbide-based bulletproof ceramic obtained in Comparative Example 1 is 2.53 g / cm 3, hardness is 28.5GPa, fracture toughness is 7.8MPa·m 1 / 2 , elastic modulus is 642GPa and flexural strength is 525Mpa.
[0061] Comparative Example 2
[0062] The preparation method of titanium diboride reinforced boron carbide-based bulletproof ceramics is the same as the preparation method in Example 6, and the specific steps refer to Example 6. Different from Example 6, in step (1) of this comparative example 2, B4C (purity of 99.5%, average particle size of 500nm) is used as the matrix raw material, TiB2 (purity of 99.9%, average particle size of 1μm) is used as the reinforcement, W powder (purity of 99.99%, average particle size of 800nm) and Ti powder (purity of 99.9%, average particle size of 5μm) are used as additives, and the ingredients are prepared according to 82.0wt% B4C, 13.5wt% TiB2, 1.9wt% W powder and 2.6wt% Ti powder.
[0063] After testing, the density of the titanium diboride reinforced boron carbide-based bulletproof ceramic obtained in Comparative Example 2 is 2.86 g / cm 3 , hardness is 33.4GPa, fracture toughness is 5.6MPa·m 1 / 2 , elastic modulus is 526GPa and flexural strength is 803Mpa.
[0064] Comparative Example 3
[0065] The preparation method of titanium diboride reinforced boron carbide-based bulletproof ceramics is the same as the preparation method in Example 6, and the specific steps refer to Example 6. Different from Example 6, in step (1) of this comparative example 3, B4C (purity of 99.5%, average particle size of 500nm) is used as the matrix raw material, TiB2 (purity of 99.9%, average particle size of 1μm) is used as the reinforcement, SiC (purity of 99.9%, average particle size of 800nm) and W powder (purity of 99.99%, average particle size of 800nm) are used as additives, and the ingredients are prepared according to 76.1wt% B4C, 13.5wt% TiB2, 8.5wt% SiC, and 1.9wt% W powder.
[0066] After testing, the density of the titanium diboride reinforced boron carbide-based bulletproof ceramic obtained in Comparative Example 3 is 2.82 g / cm 3 , hardness is 35.6GPa, fracture toughness is 6.1MPa·m 1 / 2 , elastic modulus is 559GPa, and flexural strength is 864Mpa.
[0067] Comparative Example 4
[0068] The preparation method of titanium diboride reinforced boron carbide-based bulletproof ceramic is the same as the preparation method in Example 6, and the specific steps refer to Example 6. Different from Example 6, in step (2) of this comparative example 4, the boron carbide mixture is placed in a spark plasma sintering furnace, and the gas pressure in the sintering furnace is adjusted to 40 MPa under an argon atmosphere of 1 atm, and then the temperature is increased to 1710°C at a rate of 100°C / min, kept at this temperature for 20 minutes, depressurized, and naturally cooled to room temperature.
[0069] After testing, the density of the titanium diboride reinforced boron carbide-based bulletproof ceramic obtained in Comparative Example 4 is 2.96 g / cm 3 , hardness is 37.2GPa, fracture toughness is 5.8MPa·m 1 / 2 , elastic modulus is 533GPa, and flexural strength is 834Mpa.
[0070] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0071] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A titanium diboride reinforced boron carbide-based bulletproof ceramic, characterized in that: It is composed of the following raw materials in percentage by mass: 62-82% boron carbide, 10-16% titanium diboride, 4-19% silicon carbide, 0.5-3% tungsten powder and 1-5% titanium powder; The titanium diboride reinforced boron carbide-based bulletproof ceramic is formed by spark plasma sintering; The purity of the tungsten powder is 99.9-99.99%, and the average particle size is 0.8-5.0 μm; The purity of the titanium diboride is 98.5-99.9%, and its average particle size is ≤1.0 μm; The purity of the boron carbide is 98-99.5%, and its average particle size is ≤1.0 μm; The purity of the silicon carbide is 98.5-99.9%, and its average particle size is less than 1.0 μm; The purity of the titanium powder is 99.0-99.9%, and the average particle size thereof is ≤5.0 μm; The method for preparing the titanium diboride reinforced boron carbide-based bulletproof ceramic specifically comprises the following steps: S1. Add titanium diboride, silicon carbide, tungsten powder and titanium powder to the boron carbide matrix, mix well, ball mill, and dry to obtain a boron carbide mixture; S2. Place the above boron carbide mixture in a sintering furnace, heat it to 700-900°C under vacuum conditions, then fill it with inert gas, and heat it to 1600-1800°C at 30-50MPa under the protection of inert gas, sinter it by spark plasma, and cool it naturally to room temperature to obtain.
2. The titanium diboride reinforced boron carbide-based bulletproof ceramic according to claim 1, characterized in that: In the ball milling process, the ball milling medium is anhydrous ethanol, the hard alloy balls used for ball milling are zirconia balls, the ball milling speed is 400-600 r / min, the mass ratio of zirconia balls, materials and medium is 8-12:1:1.5, and the ball milling time is 5-10 hours.
3. The titanium diboride reinforced boron carbide-based bulletproof ceramic according to claim 1, characterized in that: The vacuum degree under the vacuum conditions is -0.08MPa to -0.09MPa.
4. The titanium diboride reinforced boron carbide-based bulletproof ceramic according to claim 1, characterized in that: The spark plasma sintering time is 10 to 20 minutes.
5. Use of the titanium diboride reinforced boron carbide-based bulletproof ceramic according to claim 1 in bulletproof inserts.
Citation Information
Patent Citations
Preparation method of B4C-nanoTiB2 multiphase ceramic material
CN110386819A
High-performance boron carbide-based composite ceramic material and preparation method thereof
CN113121238A
Boron carbide-based composite material and preparation method thereof
CN114573351A